Analysis of CSF D-Dimer to Identify Intrathecal Fibrin-Driven Autoimmunity in Patients With Multiple Sclerosis. Issue 3 (8th May 2022) - Schaller-Paule, Martin A.; Yalachkov, Yavor; Steinmetz, Helmuth; Friedauer, Lucie; Hattingen, Elke; Miesbach, Wolfgang; Weber, Frank; Kirchmayr, Konstantin; Schaefer, Jan Hendrik; Foerch, Christian
Abstract : Background and Objectives: Proteins of the coagulation system contribute to autoimmune inflammation in patients with multiple sclerosis (MS). On blood-brain barrier (BBB) disruption, fibrinogen enters the CNS and is rapidly converted to fibrin, unfolding pleiotropic autoimmune mechanisms. Fibrin accumulation leads to subsequent proteolytic degradation that results in D-dimer generation. The primary objective of this study was to determine intrathecal levels of D-dimer in CSF as a measure of intrathecal coagulation cascade activation and to evaluate its diagnostic utility in patients with MS in contrast to healthy subjects. Key secondary objectives included analysis of CSF D-dimer in differential diagnoses of MS and its relation to routine clinical markers of disease activity. Methods: Patients admitted for the assessment of suspected MS were prospectively recruited from October 2017 to December 2020. Blood plasma and citrated CSF samples were analyzed using a highly sensitive luminescent oxygen channeling immunoassay. Intrathecal generation of D-dimer was analyzed by adjusting for CSF/serum albumin (Qalb ) and CSF/plasma D-dimer quotients (QD-dimer ), and corresponding CSF fibrinogen levels were determined. Final diagnoses after full evaluation and clinical data were recorded. Results: Of 187 patients, 113 patients received a diagnosis of MS or clinically/radiologically isolated syndrome. We found increased intrathecal CSF D-dimer generation levels (QD-dimer /Qalb -index) for patients with relapsing-remitting MS (RRMS; n = 71, median 4.7, interquartile range [IQR] 2.5–8.0) when compared with those for disease controls (n = 22, median 2.6, IQR 2.1–4.8, p = 0.031). Absolute CSF D-dimer values correlated with CSF fibrinogen levels (r = 0.463; p < 0 .001) and CSF leukocytes (r = 0.273; p = 0.003) and were elevated in MS patients with contrast enhancement (CE) compared with MS patients without CE on MRI (n = 48, median 6 ng/mL, and IQR 3–15.25 vs n = 41, median 4 ng/mL, and IQR 2–7; p = 0.026). Exploratory subgroup analyses indicated a correlation of intrathecal inflammatory activity and CSF D-dimer levels. Discussion: D-dimer in CSF can be reliably determined and correlates with markers of CNS inflammation and CSF fibrinogen levels. Adjusted for BBB dysfunction, CSF D-dimer may allow the identification of intrathecal coagulation cascade activation in patients with MS. Classification of Evidence: This study provides Class I evidence that CSF D-dimer levels are elevated in patients with RRMS.